Comparative Analysis of Kenyan Coal Quality and Its Global Competitiveness - (:unkn) unknown (My University, 2025)
Explorations on Kenyan Coal over the years have shown promising quantity of reserves (over 400 million tons). Experiments have been carried out to determine and compare its properties with the major world coal producers. Average quantities of Sulphur (wt.), carbon, nitrogen and hydrogen sulfide contents established as 1.63%, 59.25%, 0.95%, and 13ppm respectively. These have direct negative environmental impact and therefore need to be established, and aid in employment of technologies such sequestration, desulphurization and carbon capture. This will help in conversion of the negativities associated with coal use, which have let to stalled coal projects such as the Lamu coal project and the Mui mining that has faced serious criticism. Characterization established the average proximate quantities as; moisture content 4.25%, slightly higher than South African’s 2.70%, India’s 3.79%, but lower than Indonesian’s 5.15% and Samaranggau’s 5.65%. The volatile matter was 57.47%, this is higher than one from South Africa, India, Samaranggau and Indonesian: 26.20, 33.30, 47.67 and 46.41% respectively. Ash content as: 15.12%, this is slightly lower than South Africa’s 34.80% and higher than Indonesian’s Samaranggau’s and Indian’s 6.10, 2.61 and 7.70% respectively. Fixed carbon content: 23.18%, lower than one from South Africa, Indonesia, Samaranggau and India: 36.30, 42.34, 45.34 and 53.30 respectively. Average gross calorific value was: 24,434 kJ/kg, (grade B), is slightly lower than Indonesian’s and Samaranggau’s: 26,986.71 and 26,401.04 kJ/kg respectively, and higher than South African’s 20,526.00 kJ/kg. ASTM and ANN were mainly used for proximate and ultimate analysis results determination. Comparison analysis of the Kenyan coal and the rest of the world producers showed it being suitable for commercial and industrial exploitation, further research on geological and geochemical on Kenyan coal is recommended.
Keywords: African Research